A Short Review on Developing Membrane Proficiency for Water Energy Sustainability - Norazlianie, Sazali; M. F., Ghazali; S. A., Che Ghani; Wan Norharyati, Wan Salleh (Akademi Baru, 2020)
Growing worldwide demand in energy usage offers various opportunities in green energy technologies innovation. Responding to the sustainable energy concern is very important for the communities in order to uphold secure as well as balanced future progress ecologically and economically. Lately, increasing interest can be seen in developing enhanced efficient technologies of sustainable energy with capability to reduce the worldwide environmental footprint. Increasing knowledge in hybrid methods results in environmental resources utilization decrement during energy production. Nevertheless, numerous aspects such as natural resources availability as well as diverse policies of economic limit sustainable energies enhancement. Energy is the primary aspect in the progress to a sustainable future. Lately, technologies based on membrane start to play a crucial role in environmental-friendly and sustainable energy development. Membrane technologies opportunities in energy sustainability are analysed in review article.